2017
DOI: 10.1017/psrm.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Politically Unengaged, Distrusting, and Disaffected Individuals Drive the Link Between Compulsory Voting and Invalid Balloting

Abstract: Invalid ballots are relatively common in countries with compulsory voting, yet there is no cross-national evidence as to who is more likely to cast a blank or spoiled ballot where voting is forced. I argue that increased rates of blank and spoiled balloting where voting is obligatory result from the behavior of the politically unknowledgeable, uninterested, untrusting, and disaffected, who are incentivized to turn out to the polls where they can be sanctioned for abstention. To test this, I conduct an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 59 publications
(65 reference statements)
2
49
0
Order By: Relevance
“…Votes under compulsory voting are cast randomly, and voters are less attached to political parties and ideological convictions (Singh, 2016). Because invalid votes under compulsory voting are cast exactly by such-less engaged and less interested voters (Singh, 2017)-such invalid ballots should be considered as poor reflections of voter preferences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Votes under compulsory voting are cast randomly, and voters are less attached to political parties and ideological convictions (Singh, 2016). Because invalid votes under compulsory voting are cast exactly by such-less engaged and less interested voters (Singh, 2017)-such invalid ballots should be considered as poor reflections of voter preferences.…”
Section: Resultsmentioning
confidence: 99%
“…Invalid votes could still signify a meaningful response of politically engaged voters to a deficient political offer (Driscoll & Nelson, 2014). However, there is also substantial evidence from the study based on the cross-national survey data that invalid voting induced by compulsory voting laws is driven by a lack of information and interest, political distrust and negative attitudes toward democracy (Singh, 2017). In Latin America, invalid voting is often most frequent among those with less education and levels of political knowledge (Katz & Levin, 2016).…”
Section: The Issuementioning
confidence: 99%
“…Forced voting, in particular, has been found to magnify and entrench resentment of the democratic system (Henn and Oldfield, 2016;Singh, 2016b). The fact that compulsory voting increases invalid voting (e.g., Katz and Levin, forthcoming;Power and Garand, 2007;Singh, 2017) reinforces the notion that those who are compelled to participate in elections are less motivated to formulate a meaningful vote. This leads to our first hypothesis: Hypothesis 1: Relative to voluntary voters, those who feel compelled to vote are less likely to seek out political information.…”
Section: Theory and Hypothesesmentioning
confidence: 97%
“…In general, the increased prominence of duty under compulsory voting conforms with our expectations; however, this does not ensure more engaged political participation. As recent research has shown, compulsory voting can be linked to increases in invalid voting (Kouba & Lysek, 2016 and invalid voting can at times stem from, among other considerations, lack of interest, and disengagement (Moral, 2016;Singh, 2019). It remains to be seen whether and how more duty-driven citizens contribute to invalid voting in different contexts.…”
Section: Other Contextsmentioning
confidence: 99%